Does age influence follow-up after alcohol septal ablation in hypertrophic obstructive cardiomyopathy?. (14th October 2021) - Batzner, A; Aicha, D; Pfeiffer, B; Neugebauer, A; Seggewiss, H
Abstract: Introduction: Hypertrophic cardiomyopathy (HCM) is the most common genetic cardiac disease. Since its introduction in 1995 alcohol septal ablation (PTSMA) was discussed as treatment option only in elderly patients with symptomatic obstructive HCM (HOCM). We report on long-term follow-up after PTSMA with respect to patient's age. Methods and results: Between 5/2000 and 6/2017 we treated 952 consecutive symptomatic HOCM patients (pts) with first PTSMA in our center. 132 (13.9%) pts were <40 years of age (Group A; mean age 30.3±7.7), 421 (44.2%) pts between ≥40 to <60 years of age (Group B; mean age 50.5±5.9) and 399 (41.9%) pts ≥60 years of age (Group C; 69.6±6.3). Family history (FH) of HCM was more often seen in Group A (50% vs. 25.7% (B) and 13.3% (C); p<0.ehab724.17611) as FH of sudden cardiac death (SCD) (17.4% vs. 11.2% (B) and 7.0% (C); p<0.01). Pts in Group C were more often in NYHA class III/IV (80.7%; p<0.001 each) compared to Group A (68.2%) and B (67.9%). At the time of PTSMA an ICD for primary SCD prevention had been more often implanted in Group A (19.8%; p<0.0001) compared to Group B (10.1%) and C (5.9%). Echocardiographic measurements showed higher maximal septal thickness in Group A (23.9±5.7 mm; p<0.ehab724.17611 each) compared to Group B (20.9±4.0 mm) and C (20.1±3.5 mm). Pts of Group B had lower resting gradients (60.0±35.3 mmHg; p<0.01 each) compared to Group A (69.5±34.8 mmHg) and C (66.4±41.6 mmHg). Total heart block at PTSMA was less often seen in Group A (28.8%; p<0.05 each) compared to Group B (39.4%) and C (43.4%). Due to persistent total heart block need of permanent pacemaker implantation was lowest in Group A (3.8%, p<0.01 each) compared to Group B (9.3%) and C (14.0%) during hospital stay. One patient in Group A and C died during hospital stay, each. Follow-up was longer in Group A (6.7±5.2 years) compared to Group C (5.5±4.8 years; p<0.05) and was comparable to Group B (6.2±5.1 years). Re-PTSMA was more often performed in Group A (22.7%; p<0.01 each) compared to Group B (12.8%) and Group C (10.5%). Reported clinical improvement at latest follow-up was comparable (93.3% Group A, 93.8% Group B, and 95.5% Group C). Mortality was highest in Group C (12.5%; p<0.0001 each) compared to Group A (1.5%) and B (4.0%). In Group A no pt died from cardiac reason, whereas 5 pts died from cardiac reasons in Group B and C, each. SCD was not observed in Group A, whereas 2 pts in Group B and 1 pt in Group C suffered SCD. Conclusion: PTSMA is feasible even in young pts with symptomatic HOCM. Mortality after PTSMA is mainly due to non-cardiac reasons and more often seen in elderly pts. Especially, SCD could be observed in younger pts <40 years of age. FUNDunding Acknowledgement: Type of funding sources: None.